Revolutionizing Confined Space Work Practices in Thriving Oil and Gas Industry of Kertih, Terengganu - Ahmad Fazri, Muhammad Akram (Journal of Advanced Mechanical Engineering Applications, 2024)
The oil and gas industry is inherently known for its riskiness, involving numerous activities and a variety of chemicals naturally present in the plant environment. Simultaneously, it has been observed that certain activities, classified as critical, such as crane lifting, hydrostatics, excavations, hot work, and confined spaces, pose significant risks. Previous studies have shown that between the years 2009 and 2019, there were many reported incidents, with a total of 46 verified cases of deaths occurring in confined spaces in Malaysia. These incidents underscore deficiencies in the current system that need addressing. Therefore, this study aims to collect data on confined space incidents and issues in the oil and gas industry to propose a new intervention plan for employers and workers. The current working practices in confined spaces were analyzed for this purpose. Information and data were gathered through survey questionnaires distributed to workers employed in confined spaces. The obtained data were analyzed using the SPSS system to conduct reliability tests, ANOVA, and Pearson Correlation. The results of the ANOVA analysis indicated that there was no statistically significant difference at the p < .05 level for n = 50 concerning Age Categories, Position Categories, Years of Service, and Education Background in their perceptions of confined space work practices at Gas Processing Kertih (GPK). Additionally, Pearson Correlation analysis revealed a strong statistical correlation (r > .5, n = 50, p < .05) between Incidents at the Workplace and Health or Disease Problems. Based on the findings, suitable intervention plans have been proposed such as transparency on Incident Report by Management, quality training for confined space workers, and implementation of an efficient toolbox meeting to assist management in addressing the challenges associated with confined space working practices at GPK.